Habitual physical activity pattern of prepubescent boys and girls - Lopes, Vitor P. (2019)
The propose of this study is to identify the pattern physical activity of boys and girls during a week. The sample comprises 14 girls and 11 boys of 9.5 years of age. Physical activity was evaluated thought the computer science and applications (CSA - 7164) activity monitor, during 4 days - two-week days (Monday and Friday), and during the weekend (Saturday and Sunday). The activity monitor was worn in wrist of the non-dominant arm. After de data collection it was calculated the mean of activity per min in each day. The repeatedmeasuresMANOVAwasusedtoanalysedthechangesbetweenday's activity,and the gender differences. The results indicated a significant main effects of days, meaning that the pattern of activity change over days. The differences occurred between the Friday and Saturday, and between Saturday and Sunday. In the weekend it was registered less physical activity than in weekdays in booth boys and girls. There's no significant main effect for gender, meaning that the physical activity of boys and girls are similar. Also there's no interaction between gender and days, meaning that the changes in activity pattern was similar for booth boys and girls.